(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Polypropylene employed in plastic roofing sheets production is vulnerable to UV light irradiation, causing it to degrade. This study investigates the effect of graphite (Foreign and Nigerian) as fillers and UV stabilizers on the mechanical properties of Polypropylene subjected to UV irradiation. Polypropylene composite was prepared with varying proportions of graphite (10% to 60%). The hardness, impact strength, and tensile strength were tested before and after 48 hours of UV exposure. The results indicate that tensile strength generally decreases with increasing filler loading and UV exposure-time, though the tensile strength of Polypropylene/FGP composites at 20% filler-loading was insignificantly affected by the UV-light with its tensile-strength slightly dropping from 32.71 MPa to 31.88 MPa. Tensile strength of Polypropylene/NGP composites at 40% slightly dropped from 41.78 MPa to 37.42 MPa, likewise that of Polypropylene/NGP composites at a 90/10 proportion dropped more (33.77 MPa to 26.62 MPa) compared with that of its counterpart. The Impact strength increases with an increase in the filler-loading up to 20%, and at 30% of the filler, the materials gained more resistance to degradation by UV light. Hardness results showed that both foreign and local graphite fillers increased the material’s hardness, with PP/FGP exhibiting more consistent performance after UV exposure. The hardness value of the materials produced with 10% of the filler slightly dropped from 12.3 HRF to 11.85 after exposure. In conclusion, the composites produced offer superior resistance to degradation by UV light pertinent to Impact strength, tensile strength and Hardness of the composite compared with Polypropylene.